l'āda Ṣiyāghah Manhaj al-Dirāsah Lishuʻbati al-Lughati al 'Arabiyyati wa Ādābihā bi al-Jāmi'āt: Muqtariḥun li-Manḥaj al-Dirāsati al- Qāimi' ‘alā al'Kafā'-āti Ṭabqan li-Mutaṭallibāt al ‘Aṣr - Aḥmad Fuad Afandī (Al-Jami'ah: Journal of Islamic Studies, 2004)
The Globalization and Industrialization era demand a high quality graduate in relevant competen with people's demand, including working world. In order to answer the challenge, a curriculum formulation for Arabic language and literature in University is necessary which is oriented to increasing a quality of graduate and based on the result of people's demand analysis, beside main topics of Arabic study analysis. This curriculum should be flexible which is possible to elaborate some competence options based on people demand and interest / talent of student. It is consists of (1) Scientific Materials (linguistic, literature and culture of Arab), (2) Language skills (listening, speaking, readings, writing), (3) Main expertise / profession ( 4) Support expertise / profession and (5) Religion and social.